Percutaneous transluminal angioplasty in the treatment of renovascular hypertension: sequential prospective study - Miranda Jr., Fausto (1998)
OBJECTIVE: to evaluate the use of percutaneous transluminal renal angioplasty (PTRA) in the treatment of renal vascular hypertension. DESIGN: sequential prospective PTRA treatment of severe arterial hypertension, screening by the captopril test, confirmed by renal arteriography, and the result evaluated by post-PTRA arteriography, blood pressure measurement and renal function. SITE: Vascular Surgery, angioradiology sector, and Nephrology outpatients department of the Federal University of São Paulo - Paulista School of Medicine, São Paulo, Brazil, a tertiary health-care institution. PARTICIPANTS: PTRA was employed on 32 patients screened by clinical examination, captopril test and renal arteriography. EVALUATION: PTRA results were evaluated by the criteria of the Cooperative Study of Renovascular Hypertension. RESULTS: after PTRA the completion arteriography showed no renal stenosis in 24 patients (75%), residual stenosis (20-50%) in 3 (9.4%) and no change in 5 (15.6%). The blood pressure results were: 3 patients (9.4%) were cured, 24 (75%) improved: and 5 (15.6%) were unchanged. We observed normal renal function before and after PTRA in 25 patients (78%); altered pre- and improved post-PTRA in 2 (6.3%); post-PTRA remained unaltered in 2 (6.3%); and altered pre- and worsened post-PTRA in 3 (9.4%). Recurrence of stenosis occurred in one patient after 8 months. CONCLUSIONS: PTRA is a convenient procedure, relatively safe and an effective complementary method of medical therapy for controlling renovascular hypertension.